Comparing the usage of autologous blood transfusion with homologous blood transfusion in spine surgery (Medical Journal of Indonesia, 2004)
Autologous Blood Transfusion (ABT) is the safest type of blood transfusion for the operator and the patient. The preoperative donation technique had already been reduced the homologous blood requirements successfully. Homologous Blood Transfusion (HBT) brings more risks in complications such as transmission of diseases, anaphylactic reactions, haemolitic reactions etc. This was a parallel study, comparing one group receiving ABT and a second group receiving HBT where in both groups were performed spine surgery. The parameter used was the hemoglobin(Hb) and hematocrit(Ht) content preoperatively (after donation of ABT) and after transfusion, total days in hospitalization after surgery. Another purpose of this study was also to achieve understandings in using ABT by considering the total patients who finally required additional HBT. There were 74 patients with diagnosis of spine fracture, tuberculous spondylitis, scoliosis, spinal stenosis and spondylolisthesis. In the ABT group the average age was 33,9 ± 14 years old and the HBT group was 29,1 ± 11,5 years old. Both groups consisted of 21 males and 16 females. Body weight of the ABT group was 55,3 ± 11,1 kg and the HBT group 52,8 ± 9,7 kg. Amount of donations preoperatively in ABT was 798,6 ± 170 cc. There were 12 patients (32,4%) where the donated blood amount preoperatively did not match up the requests. There were eight patients (21,6%) in the ABT group that required additional HBT of about 550 cc. Three patients (8,1%) of the ABT group received transfusion that did not match the indications (blood loss < 15% of the total blood volume). The Hb and Ht content preoperatively (after donation) of the ABT group significantly was less than the HBT group (p= 0,001). Hb content after transfusion in the ABT group was not significantly less than the HBT group (p = 0,30). Hospitalization days after surgery were significantly higher in the HBT group (p = 0,000). In conclusions : there was 21,6% of the ABT group with the preoperative donation technique that finally required additional HBT. Also there was no difference in the Hb and Ht content preoperatively and post transfusion in the ABT and HBT group, whereas hospitalization days after surgery were higher in the group receiving HBT than in the group receiving ABT. (Med J Indones 2004; 13: 17-23) Keywords: autologous blood transfusion, homologous blood transfusion, spine surgery